A new international journal for rapid publication of botanical taxonomy - Christenhusz, M; Chase, M W; Fay, M F; Lumbsch, T; Monro, A; Vorontsova, M; Zhang, Z Q (Phytotaxa, 2009)
We are pleased to present you with the first issue of Phytotaxa, a new international journal for botanical taxonomy. Descriptive taxonomy—the discovery and description of taxa—is fundamental to biology and documentation of biological diversity (Wheeler 2007). With the current need to document and monitor biological diversity enshrined in international conventions (e.g. Convention on Biological Diversity, Convention on Migratory Species, 2010 Millennium Development Goals) it is unfortunate that descriptive taxonomy finds itself marginalised within the scientific community and even in traditional centres of excellence such as natural history museums and universities (Zhang 2006). There is widespread perception among non-taxonomists that description of our flora and fauna was already completed years ago. This contributes to the bias against publications of new taxa.